Structural change and regulatory reform in the utilities industries - Trebing, Harry M. (American Economic Review, 1980)
Regulatory reform is best achieved by recognizing the infirmities inherent in the traditional application of prices/earnings controls, especially when such controls are applied in a narrow context that ignores market-structure considerations. A new set of pressures can be introduced by broadening the perspective of regulation to include structural and distributional considerations. This will enhance industry performance and augment the effectiveness of the regulatory process.